Intrathoracic axial osteosarcoma - Gomide, Paula Regina Silva [UNESP]; Brandão, Cláudia Valéria Seullner [UNESP]; Babicsak, Vivian Rocco [UNESP]; Minto, Bruno Watanabe [UNESP] (Universidade Federal do Rio Grande do Sul, 2018)
Background: Bone tumors have a challenging diagnosis and treatment. Osteosarcoma is the name given to a heterogeneous group of malignant, agressive and invasive tumors that often determine bone lysis. Almost all of the animals develop lung metastases, progressing to death. Usually affect the appendicular skeleton, but can also occurs in others areas, although these presentations are rare. Prognosis is always poor. The aim of this paper is to report a case of a dog with osteoblastic osteosarcoma of the sternum, which was diagnosed by computed tomography and histopathologic analysis after excisional biopsy. Case: A male Cocker Spaniel dog, weighing 25 kg, elderly, was examined at the Veterinary Hospital. As main complaint was reported soft swelling on the ventral cervical region causing dyspnea. The patient had previously been medicated with dexamethasone with a significant decrease in the swelling, however recurrence was observed with the cessation of the treatment. Due to the presence of heart murmur, patient underwent to chest radiography and eletrocardiography. Images showed a tumor in the sternal lymph node region, displacing the heart caudally, trachea and esophagus dorsally, causing cranial edema due to a compression of the venous return by the cranial vena cava and subsequent dyspnea. Furosemide (Lasix®) was administered during ambulatorial treatment and prescribed to home, with satisfactory results, with decreased edema and consequent improvement of respiratory symptoms. It was decided to perform computed tomography to better design of the chest structure. The structure located in cranial thoracic region measured about 10.5 cm long x 5.8 cm high x 8.4 cm wide. The patient was undergone to sternotomy to remove the mass that was closely adhered to the sternum and pericardium. The pericardectomy and sternum removal were not performed due to animal being old and present metabolic and cardiopulmonary conditions. Some samples were collected for histological examination resulting in osteoblastic osteosarcoma. After surgical treatment, the patient showed improvement of dyspnea, more active and no signs of pain at the surgical site. Due to the unfavorable result of the histopathological analysis, it was decided to star chemotherapy. The protocol chosen was carboplatin (Carboplatino®) as a single drug, every 21 days totalizing four applications as recommended by literature. Two cycles of carboplatin were done as adjuvant chemotherapy. The patient supported the treatment very well without any clinical or laboratory abnormality. Any radiographic signs of pulmonary metastasis or local recurrence was seen, however, after 18 months of survival, the patient died of non-related cause. Discussion: Osteosarcoma is the most commonly diagnosed bone tumor in dogs. Intense dyspnea and the swelling in the submandibular region was due to the compression of thoracic structures by the size of the tumor and the internal location within the chest. The cranial swelling is due to the syndrome caval that is rare in veterinary medicine and is describe in some specific conditions. Computed tomography was performed to better tumor delineation, as it is an important tool to assess the extent of the tumor and other characteristics, allowing optimal surgical planning for each case. Histophatological diagnosis of osteoblastic osteosarcoma is characterized by new bone formation that appears radiographically with increased radiopacity, as observed in all images. Gold standard treatment of neoplasms is the association of surgical excision followed by chemotherapy, which was effective in this case reported, since it provided quality of life during 18 months, three times higher than the majority of cases reported in the literature, being death due to causes unrelated to the tumor.
Osteossarcoma axial intratorácico
Keywords: Bone; Cancer; Chemotherapy; Dog; Surgery